Clinico-laboratory profile and mortality in plasmodium falciparum and vivax malaria in a tertiary centre - Dr. Prashant Chaudhary; Dr. Saurabh Piparsania; Dr. Nagesh Chandra Doharey (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Malaria is a disease of global health importance and currently, 95% of the Indian population lives in malaria endemic area. Malaria parasite profile has been changing significantly over the years and is responsible for significant mortality and morbidity.Objective: To study the clinic-hematological profile and mortality in plasmodium vivax and falciparum malaria.Methodology: Hospital based observational study in a tertiary care centre for a period of 4 years including children <14 years of age who were tested positive for plasmodium vivax/falciparum.Results: A total of 230 confirmed cases of malaria were taken up, of which 141 were P. falciparum (61.30%) and 69 were P. vivax (30%) positive. 20 patients were positive for both Pf and Pv (8.70%). Fever with chills and/or rigor was most common symptom and pallor followed by splenomegaly was the most common physical signs. The most common hematological abnormality noted was anemia followed by thrombocytopenia. Anemia was more common in p. falciparum and in children below 5 years of age. Mortality was highest in p. falciparum malaria (5.67%) followed by mixed infection (5%) and Pv (2.89%). Cerebral malaria was most common cause of mortality (6 cases) followed by acute renal failure and shock. Complications were more common with Pf group, though they were also seen in Pv group.Conclusion: Cerebral malaria is the most lethal entity of severe malaria and children are more prone than other susceptible groups. Encephalopathy, shock and renal failure at the time of presentation were poor prognostic factors, while anemia and thrombocytopenia were not found to be associated with adverse outcome.